Effect of Operating Parameters on the Active Chlorine Production in Bipolar Electrochlorination Cell with Titanium and Platinum/Titanium Anode Electrodes using Box-Behnken Method - Samaneh Dehghan; Yousef Dadban Shahamat; Fariba Ziarati (تحقیقات سلامت در جامعه, 2022)
Introduction and purpose: Today, chlorine and its compounds are the most popular elements employed for disinfecting water and wastewater due to their flexibility, cost-efficiency, and ease of use. This research aimed to optimally produce active chlorine by the electrochlorination method using titanium and platinum/titanium electrodes. Methods: This experimental study was conducted in a batch flow of an electro-chlorination cell. The experimental design was performed using the Box Behnken method with a sample size of 34 experiments. The production of active chlorine was evaluated and compared on various operating factors, including current density (10-60 A/dm2), sodium chloride concentration (50-250 g/L), reaction time (5-120 min), and two types of anode electrodes of titanium and platinum/titanium and 316 cathode steel. Results: The results showed all four operating parameters had a significant effect on the active chlorine production and the highest effectiveness was related to electrolysis time, followed by current density, sodium chloride concentration, and anode electrode in descending order. The optimal operating conditions provided by the model for chlorine production included the electrolysis time of 120 min, current density of 60 A/dm2, concentration of sodium chloride of 187 g/L, and type of platinum/titanium anode electrode and 316 cathode steel electrode, which resulted in active chlorine of 65.95 g/L. Conclusion: This method can be used as an effective method to produce chlorine to disinfect water and wastewater in treatment plants, and if replaced with gas chlorination systems, the safety problems of chlorine gas capsules will be solved.